Required Elements for Next-generation Prognostic Index beyond Left Ventricular Ejection Fraction in Heart Failure - Hoshida, Shiro (Journal of Cardiology and Cardiovascular Medicine, 2024)
Many reports are showing no differences in prognosis between patients with Heart Failure (HF) with preserved and reduced ejection fraction. All-in-one analysis with a multivariable model, including clinical characteristics, blood test, comorbidity, and echocardiographic indices, on clinical outcomes in patients with HF has not been performed rarely in previous studies. We have to accept the need to be more comprehensive in the outcome analysis of patients with HF and consider the intricate interplay of multiple variables in patient outcomes.